BERPIKIR KRITIS : STUDENT CENTERED LEARNING (SCL) DAN RECIPROCAL TEACHING - Yuyun Suhariami; Lilik Sri Hariani; Riril Mardiana Firdaus (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
This study discusses the Student Centered Learning (SCL) Approach, Reciprocal Teaching Learning Model, and Critical Thinking Ability in Ma'arif 02 Islamic Middle School Malang, This study aims to analyze: (1) The Effect of the Student Centered Learning (SCL) Approach, Model Reciprocal Teaching Learning on Critical Thinking Ability in Grade VIII Students of Ma'arif 02 Islamic Middle School Malang City (2) The Effect of Student Centered Learning (SCL) Approach on Critical Thinking Ability in Students (3) The Effect of Reciprocal Teaching Learning Model on Thinking Ability learners. This research uses a quantitative approach, this type of research is ex post facto. The statistical method of research uses multiple linear regression. The population in this study were students of class VIII 2018/2019 school year, with the use of research sampling techniques that are simple random sampling with a total of 100 students or 30% of the population. Data analysis techniques in this study used the classical assumption test. The results of this study indicate that there is a positive effect on the approach of student centered learning and reciprocal teaching learning models on critical thinking skills. The results of this study concluded that the student centered learning approach and the reciprocal teaching learning model can influence students' thinking skills